Current Issues of Patriotic Education - Fayzilvaxobovich, Sarimsakov Madaminjon (Journal of Innovation in Education and Social Research, 2025)
This article provides information on strengthening the sense of patriotism and Motherland among young people, on how to make their needs for spiritual maturity strong and sustainable, and patriotic education is considered a sign of spiritual maturity, an important factor in the development of society, strengthening the spiritual foundations of independence.